"Commentarium in Apocalypsin". Number and Geometric Form in the Illustrations of the «Beatus» of Saint Mamas of Lorvão - de Oliveira Dias, Ana (Eikón / Imago, 2015)
For centuries number and geometry were seen as the fundamental elements of medieval spirituality, and were considered by early Greek and Latin theologians to be the key to achieving true enlightenment about creation and divine revelation. Taking as our central subject the only illustrated Portuguese copy of the early medieval work Commentarium in Apocalypsin of Beatus of Liébana, from the scriptorium of Saint Mamas of Lorvão, this study provides an analysis of symbolic imagery based on number and geometrical form expressed in the iconographic and iconological programme of this late manuscript from the Hispanic Beatus tradition. In this perspective, we attempt to describe the crucial role played by the «science of number», not only in the conception but also in the reception of this work and of its spiritual message, and how these features reinforce the antiquity of this pictorial model.